Mark: arise and follow the son Expository expository reflections on the Gospels - O'Donnell, Douglas Sean (Expository reflections on the Gospels, 2024)
"Offers 47 chapters of sermonic commentary on every passage from the Gospel of Mark. These expositions offer insights into the historical setting and the original audience, discuss the grammatical and exegetical style of Mark and apply the Gospel to modern life"--